Effect of dietary serine supplementation on performance, egg quality, serum indices, and ileal mucosal immunity in laying hens fed a low crude protein diet - Jian-min Zhou (Elsevier, 2021)
ABSTRACT: This study was designed to evaluate the effect of dietary Ser on performance, egg quality, serum indices, and ileal mucosal immunity in laying hens fed low crude protein (LCP), essential amino acids (EAA) balanced diets. A total of 480 Hy-Line Brown layers at 24 wk of age were randomly assigned into 5 dietary treatments with 8 replicates of 12 birds each. Treatments included a control diet (16.49% CP), and 4 LCP, EAA balanced diets (14.05% CP) supplemented with 0, 0.114%, 0.306%, 0.498% L-Ser, respectively. Dietary Ser supplementation linearly increased hen-day egg production (HDEP; P < 0.05) and decreased feed-to-egg ratio (P < 0.05) among LCP groups from wk 6 to 10, and the optimal HDEP of layers occurred at Ser level of 0.498%. At the end of wk 10, birds in the control had higher albumen height and thick white proportion than those fed the LCP diet without Ser addition (P < 0.05), and presented a lower yolk color score than all LCP groups (P < 0.05). Among LCP groups, serum total protein and globulin contents were significantly increased by dietary Ser addition at the levels of 0.306% and 0.498% (P < 0.05), and had a linear response to the supplemental Ser levels (P < 0.05). Furthermore, dietary 0.498% Ser supplementation significantly increased serum immunoglobulin G and immunoglobulin M contents (P < 0.05) and up-regulated the expression of mucin 2, secretory immunoglobulin A, and relevant glycosyltransferases of O-glycosylation in ileal mucosa (P < 0.05). The increased expression of proinflammatory cytokines IFN-γ and IL-1β induced by LCP diets (P < 0.05) was reversed following 0.498% Ser addition (P < 0.05). Collectively, dietary CP reduction by 2.44% could maintain the productive performance of layers when it was fortified with certain EAA, though poor albumen quality, and ileal inflammation were occurred. The addition of Ser to LCP diets improved performance probably through enhancing humoral and ileal mucosal immunity and attenuating the ileal inflammation of layers.